A new approach to improving the macrosegregation in zirconium‐containing magnesium‐lithium alloy: Eine neue Herangehensweise zur Verbesserung der Makroseigerung in zirkoniumhaltigen Magnesium‐Lithium‐Legierungen. Issue 9 (3rd September 2018) - Wang, L.; Guan, H.; Wu, G.; Pan, Y.; Sun, S.
Abstract: In the preparation process of zirconium‐containing magnesium alloy, although zirconium is introduced into alloy by magnesium‐zirconium master alloy, the settling of zirconium particles has always been a key problem. In this study, the magnesium‐30wt.%zirconium master alloy was added into magnesium‐14wt.%lithium‐zinc alloy melt in the form of the block (about 20 mm) and the particles (about 20 μm), respectively, and then magnesium‐14wt.%lithium‐zinc with 0.5 wt.% zirconium alloy were prepared using stir‐casting process. Macrosegregation of major element (zirconium), microstructure and microhardness at different casting positions were examined to investigate the effect of zirconium addition methods on macrosegregation of magnesium‐14wt.%lithium‐zinc alloy. The results show that, for the block magnesium‐zirconium master alloy addition, there is obvious macrosegregation in alloy ingots, the zirconium contents at the top position of ingot are higher than that at the bottom by nearly 200 %. The method of particles master alloy addition can effectively improve macrosegregation, the difference in zirconium contents between the top and bottom is less than 16 %.